Pension systems and retirement incomes across OECD countries - Disney, Richard; Johnson, Paul (Cheltenham, UK ; Northampton, MA : E. Elgar Pub., 2001)
An analysis of the pension reform process in nine countries. It examines the policy reform process in each country, against the background of the fiscal stresses arising from ageing populations. It also explores whether different pension delivery systems generate different standards of living.
Includes bibliographical references and index.
oif 08/08/16
Loan
Keywords: Old age pensions; Pensions; Social security; Older people; Retirement income